2019
DOI: 10.1177/2158244019829548
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory Factors of the Environmental Disclosure of Potentially Polluting Companies: Evidence From Brazil

Abstract: When a company conducts environmental disclosure, it increases communication and reduces the asymmetry of information, so that customers, suppliers, investors, civil society, Government, scientific community, and others may have access to the information (Husted & Sousa-Filho, 2018; Rosa, Ensslin, Ensslin, & Lunkes, 2011; M. A. Souza, Rásia, & Jacques, 2010). In Brazil, one of the ways to disclose the information on open capital companies is making the sustainability report (RSUST) available (Calixto, 2013). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…Some studies tried to establish relationship between CEDs and corporate characteristics. [28][29][30][31] While most of the studies found positive relationship between CEDs and company's size and profitability; some worksalso found variables like leverage, ISO 14001 certification and auditors to have some impact on these disclosures. Public holding of shares, and constitution and size of board of directors were not found to have significant impact on CEDs.…”
Section: Theoretical Background and Objectives Of The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies tried to establish relationship between CEDs and corporate characteristics. [28][29][30][31] While most of the studies found positive relationship between CEDs and company's size and profitability; some worksalso found variables like leverage, ISO 14001 certification and auditors to have some impact on these disclosures. Public holding of shares, and constitution and size of board of directors were not found to have significant impact on CEDs.…”
Section: Theoretical Background and Objectives Of The Present Studymentioning
confidence: 99%
“…In a study to identify factors responsible for 182 Brazilian potentially polluting companies' environmental disclosures in annual reports from years 2005 to 2015, Santos et al 29 observed that among other things, companies with larger size and higher profit disclosed more environmental information. However, companies whose auditor was either one of the Big Four, whose size of board of directors was big and consisted of higher numbers of independent directors, and who had shareholdings more dispersed did not disclose more environmental information, indicating that these factors were not explanatory to environmental disclosures by the sample companies.…”
Section: Theoretical Background and Objectives Of The Present Studymentioning
confidence: 99%
“…O IBRACON, por sua vez, criou a Norma e Procedimento de Auditoria, em 1996, recomendando que os ativos e passivos ambientais sejam divulgados em títulos específicos, nas demonstrações contábeis das empresas. Já o Conselho Federal de Contabilidade (CFC) aprovou a Norma Brasileira de Contabilidade Técnica 15 (NBC T15), que institui a Demonstração de Informação de Natureza Social e Ambiental (CARNEIRO; DE LUCA; OLIVEIRA, 2008;PIRES;SILVEIRA, 2008;SANTOS et al, 2019).…”
Section: Evidenciação Ambientalunclassified
“…Regarding the use of the heavily polluting industries, one reason is that heavily polluting entities are the focus of the environmental regulations of the Chinese government and the targets of media and investor attention. Accordingly, extant literature on EID has focused on the heavily polluting industries (e.g., Jaggi et al, 2017;Santos et al, 2019;Zheng et al, 2020). More importantly, according to the statistics of our sample, media coverage and investor attention on EID are largely concerned about the heavily polluting industries.…”
Section: Introductionmentioning
confidence: 98%